Did helminths guard against autoimmune conditions? - Mohsin Abdulhussein Hasan; Hujran Abdulraheem Abed; Hawraa Hamid Hussein; Anas E Almousawi; Roaa Noori; AliHayder Talib Mahdi; Zainab Khaleel Ibrahim (Genius Journals, 2022)
Long-lived multicellular parasites known as helminths cause their hosts' immune systems to respond strongly and distinctly. The buildup of parasite loads over time, the infection's chronicity recurrence, and the dominant function of immunity in pathogenesis are typical characteristics of helminth infections
Keywords: Helminths; immune systems; recurrence